Social and Organizational Perception Towards Women Police: A Study of Metropolitan Police in Bangladesh (Bangladesh Journal of Public Administration, 2024)
This study has examined the societal and organizational outlooks toward female police currently working in the Sylhet metropolitan area of Bangladesh. As the social activity of women increases, societal attitudes toward them are changing, and as an institution, the police department has included several facilities over the years. Now the question is, are these things really happening? To better understand the actual scenario of women police in the Metropolitan area, this study has interviewed 13 field-level officials using purposive sampling from the Sylhet Metropolitan Area through a semi-structured questionnaire. This study found that society's mental inertia and behavioural attitudes toward women have significantly impacted the current situation of female cops in metropolitan police. The public still needs to comprehend women working in such outfits, who must face various struggles to join the force. They often face physical difficulties with tasks, and their male counterparts do not always accept them easily. Although organizational facilities have increased in many areas, there are some problems regarding daycare centres, maternal leave, and separate washroom facilities. Thus, this study recommends improving their facilities based on female cops' capabilities.